World Cities Report 2022 - United Nations Human Settlements Programme (United Nations, 2022)
World Cities Report 2022: Envisaging the Future of Cities seeks to provide greater clarity and insights into the future of cities based on existing trends, challenges and opportunities, as well as disruptive conditions, including the valuable lessons from the COVID-19 pandemic, and suggest ways that cities can be better prepared to address a wide range of shocks and transition to sustainable urban futures. The Report proposes a state of informed preparedness that provides us with the opportunity to anticipate change, correct the course of action and become more knowledgeable of the different scenarios or possibilities that the future of cities offers. The Report reaffirms that the vision for the future of cities must embody the “new social contract” in the form of universal basic income, universal health coverage and universal housing and basic services.